The Effect of Brand Image and Price on Tourist Purchasing Decisions Choosing The Westin Resort Nusa Dua Bali as a Mice Venue - Wedari, Ni Kadek Maedha; Pitanatri, Putu Diah Sastri; Wiartha, Nyoman Gede Mas (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The tourism industry has great potential in generating foreign exchange and improving the welfare of the community. MICE (Meeting, Incentive, Convention, and Exhibition) is a rapidly growing sector in this industry. The MICE industry in Indonesia has been severely impacted by the COVID-19 pandemic, with many events postponed or canceled, affecting related economic sectors. Recovery of the sector requires strategies to adapt to the "new normal", event innovation, implementation of health protocols, and utilization of technology. Understanding brand image and personality is important for employees in creating a positive company image, such as at The Westin Resort Nusa Dua Bali. This study uses quantitative methods to evaluate the effect of brand image and price on purchasing decisions. The results showed that brand image and price have a positive but significant influence on purchasing decisions.